State Ownership and Firm Performance: Evidence From the Chinese Listed Firms - Le, Trien; Chizema, Amon (Organizations and Markets in Emerging Economies, 2011)
Based on a sample of Chinese listed firms, this paper seeks to understand the role of state ownership on firm performance (accounting-based returns) and firm value (market-based indicators). Results show that state ownership is positively associated with firm performance. In addition, state ownership has a moderating effect on the association between firm performance and firm value. At low levels of state ownership, firm performance is negatively associated with firm value. However, at high levels of state ownership, the association becomes positive. Drawing on signaling theory, the study helps to understand the role of state ownership in the association between firm performance and firm value, an area that has received minimum attention in research.Specifically, state ownership may be a strategic asset for Chinese listed firms boosting accounting returns but perceived differently by the market.Given the current levels of state ownership in many transitional economies, this study sheds light for policy makers on the effects of high or low levels of state ownership on firm performance and value. Moreover, the study may assist would-be investors who may contemplate investing in privatized SOEs, in China or other countries with similar institutional arrangements.